2009
DOI: 10.1029/2008jd011244
|View full text |Cite
|
Sign up to set email alerts
|

Concentric gravity waves in the mesosphere generated by deep convective plumes in the lower atmosphere near Fort Collins, Colorado

Abstract: [1] Gravity waves in the mesopause region (80-105 km) may induce perturbations in OH Meinal Band emissions at $87 km. These perturbations can be observed by ground-based OH airglow imagers. In this paper, we present observations of concentric gravity waves (CGW) by the all-sky OH imager at Yucca Ridge Field Station (40.7°N, 104.9°W) near Fort Collins, Colorado. We find that expanding rings of concentric gravity waves were observed on 9 out of 723 clear nights from 2003 to 2008. In particular, on 11 May 2004, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
248
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(271 citation statements)
references
References 45 publications
22
248
1
Order By: Relevance
“…A wider angular-range analysis further indicates that the fluctuations propagate away from the storm. The fluctuation periods, possible propagation speed, and inferred propagation direction are consistent with recent observations and model studies of atmospheric gravity waves (AGW) at the D-layer altitude that are originated from convective thunderstorm activity overshooting the tropopause [Alexander et al, 1995;Vadas and Fritts, 2004;Vadas et al, 2009;Yue et al, 2009]. From LASA's own observations of some intracloud discharges (e.g., NBEs), it was noticed that several intermittent clusters of events elevated to 15 km or higher in this storm, suggesting that corresponding convection cells overshot the local tropopause.…”
Section: Summary and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A wider angular-range analysis further indicates that the fluctuations propagate away from the storm. The fluctuation periods, possible propagation speed, and inferred propagation direction are consistent with recent observations and model studies of atmospheric gravity waves (AGW) at the D-layer altitude that are originated from convective thunderstorm activity overshooting the tropopause [Alexander et al, 1995;Vadas and Fritts, 2004;Vadas et al, 2009;Yue et al, 2009]. From LASA's own observations of some intracloud discharges (e.g., NBEs), it was noticed that several intermittent clusters of events elevated to 15 km or higher in this storm, suggesting that corresponding convection cells overshot the local tropopause.…”
Section: Summary and Discussionsupporting
confidence: 66%
“…Ionospheric studies have found evidence of D-layer heating due to thunderstorm quasi-electrostatic fields [Inan et al, 1996;Pasko et al, 1995], evidence of direct heating of the D-layer due to lightning electromagnetic pulses [Cheng and Cummer, 2005;Cheng et al, 2007], and evidence of atmospheric gravity wave (AGW) influence on the E-region ionosphere (100-150 km) [Davis and Johnson, 2005;Johnson and Davis, 2006]. Stratospheric AGW studies have shown neutral density fluctuations at altitudes of 60-90 km due to tropospheric thunderstorms activities [Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Yue et al, 2009], and the electron density at this altitude is expected to fluctuate in a similar manner. However, because of low electron densities in the D-layer, it is difficult to continuously measure the electron density and its possible spatial and temporal fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Note that concentric rings from convective storms, like those in Fig. 6, have been occasionally observed in the OH airglow layer from deep convection (Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Suzuki et al, 2007;Yue et al, 2009). …”
Section: Gravity Wave Excitation From Convective Plumesmentioning
confidence: 99%
“…The convective plume model, ray trace model, and reconstruction methods described in this paper have been recently applied to the modeling of an observed deep, convective plume near Fort Collins, Colorado, which produced nearly concentric rings in the OH airglow layer for ∼1.5 h (Yue et al, 2009). Using radar measurements and satellite imagery, we estimated that this plume had a width of D∼15 km, a depth of D z ∼10 km, a duration of σ t ∼10 min, and an updraft velocity of w pl =35 m s −1 .…”
Section: Reconstruction and Normalization Of The Wave Field In Real Smentioning
confidence: 99%
“…Thunderstorms trigger a broad spectrum of gravity waves via latent heat release and interactions with the mean flow (37). In the early spring and fall, when wind speeds and shear in the middle atmosphere are at a climatological minimum (38), the initial structure of the waves is preserved, resulting in concentric rings of nightglow (39). Fig.…”
Section: Suomi Makes a Splash With Global Nightglow Imagerymentioning
confidence: 99%